1985
DOI: 10.1111/j.1464-410x.1985.tb06307.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Follow‐up after Transurethral Prostatic Resection With or Without a Short Peri‐operative Antibiotic Course

Abstract: This study was undertaken to analyse the results in 192 patients who 3 to 4 years earlier had undergone transurethral resection (TUR) in a controlled clinical trial on the value of a short peri-operative course of antibiotics. The survival rate was comparable in both groups. Most deaths were due to cardiovascular disease and/or cancer of the prostate and the gastrointestinal tract. Infectious events predominated in the control group and more antibiotics were prescribed for these patients during follow-up than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1986
1986
1996
1996

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
0
4
0
1
Order By: Relevance
“…Longterm follow-up studies found that the condition was transient and tended to resolve spontaneously after catheter removal without any further treatment (Hirschmann and Inui, 1980;Grabe, 1987). However, some complications such as urethral stricture and bladder neck stenosis (Grabe and Hellsten, 1985;Hammarsten et al, 1989), secondary haemorrhage (Harvey er a[., 1986), bacteraemia (Sullivan et al, 1973), septicaemia (Cafferkey et al, 1982) and epididymitis (Genster and Madsen, 1970) were reported, although direct evidence to link bacteriuria with these complications is lacking. This perhaps explains why only 10% of urologists in the UK use routine antimicrobial prophylaxis with prostatectomy (Wilson and Lewi, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Longterm follow-up studies found that the condition was transient and tended to resolve spontaneously after catheter removal without any further treatment (Hirschmann and Inui, 1980;Grabe, 1987). However, some complications such as urethral stricture and bladder neck stenosis (Grabe and Hellsten, 1985;Hammarsten et al, 1989), secondary haemorrhage (Harvey er a[., 1986), bacteraemia (Sullivan et al, 1973), septicaemia (Cafferkey et al, 1982) and epididymitis (Genster and Madsen, 1970) were reported, although direct evidence to link bacteriuria with these complications is lacking. This perhaps explains why only 10% of urologists in the UK use routine antimicrobial prophylaxis with prostatectomy (Wilson and Lewi, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteremia may turn into septi cemia, the most serious hazard following ma nipulation of the urogenital tract. Postopera tive bacteriuria has been reported to develop in about 20-60% of preoperatively nonbacteriuric patients under no chemoprophylaxis [7][8][9][10][11][12][13][14][15], Concerning the importance of postop erative bacteriuria, Grabe and Hellsten [15] reported that bacteriuria was associated with an increased risk for further severe infectious events, and stricture of the urethra and blad der neck. Although many studies have focused on antibiotic use in prostatectomy, the ratio nal use of antibacterial agents in view of the potential seriousness of the postoperative in fectious complications remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly Grabe & Hellsten, in a group of patients who 3 4 years earlier had had TURP in a controlled trial on a short course of perioperative antimicrobics (191, found that infectious events predominated in the control group during follow-up, and the frequency of postoperative urethral stricture formation was significantly higher in that group (20).…”
Section: Risk Factors For Uti In Connection With Turpmentioning
confidence: 94%